1997
DOI: 10.1007/s11626-997-0144-9
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1 induces growth arrest and apoptosis but not ciliated cell differentiation in rat tracheal epithelial cell cultures

Abstract: We are studying the regulation of ciliated cell differentiation using an in vitro model of tracheal regeneration. Previously, we reported that removal of growth stimulating compounds such as epidermal growth factor (EGF) and cholera toxin reduced DNA synthesis and cell number while increasing ciliated cell differentiation (Clark et al., 1995). This result suggested that the induction of growth arrest may stimulate terminal differentiation of airway epithelial cells into ciliated cells. Transforming growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…TGF-␤ induces growth arrest and apoptosis of airway epithelial cells. 27 Our laboratory and others have shown that the integrity of the epithelium is critical in preventing the development of the OB-like lesion in the mouse tracheal transplant model. 13,28,29 Stabilization of the epithelium may prevent the formation of granulation tissue.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…TGF-␤ induces growth arrest and apoptosis of airway epithelial cells. 27 Our laboratory and others have shown that the integrity of the epithelium is critical in preventing the development of the OB-like lesion in the mouse tracheal transplant model. 13,28,29 Stabilization of the epithelium may prevent the formation of granulation tissue.…”
Section: Discussionmentioning
confidence: 95%
“…The results suggest that pirfenidone may be worthy of further evaluation for its effectiveness in preventing or ameliorating OB in lung transplant recipients. Pirfenidone's mechanism of action probably involves TGF-␤; however, pirfenidone is known to interfere with other mediators of fibrosis [23][24][25][26][27][28][29][30][31][32][33][34] and thus additional investigations of its effects on these and other mediators of rejection are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-␤ stimulates proliferation of mesenchymal cells but inhibits that of endothelial (12) and epithelial cells (13). TGF-␤ is also known to inhibit the proliferation of a variety of cancer cell lines including the human breast cancer cell line MCF-7 (14,15).…”
Section: Connective Tissue Growth Factor (Ctgf)mentioning
confidence: 99%
“…Deregulation of the TGF-h signaling is frequently detected in numerous human malignancies due to either loss of expression or mutational inactivation of its membrane receptors or intracellular Smad proteins (3)(4)(5)(6)(7). TGF-h serves as a growth suppressor by inducing cell growth arrest and promoting apoptosis (8)(9)(10); during tumorigenesis, loss of growth inhibitory control permits tumor cells to use TGF-h for evasion of immune surveillance and gain of metastatic ability (11)(12)(13). The mechanistic network underlying the molecular switch from TGF-h acting as a tumor suppressor to functioning as a tumor promoter during the metastatic process is not clearly defined.…”
Section: Introductionmentioning
confidence: 99%